Emerging Organometallic Methods for the Synthesis of C‐Branched (Hetero)aryl, Alkenyl, and Alkyl Glycosides: C−H Functionalization and Dual Photoredox Approaches. Issue 2 (19th October 2020) - Ghouilem, Juba; de Robichon, Morgane; Le Bideau, Franck; Ferry, Angélique; Messaoudi, Samir
Abstract: Transition‐metal‐catalyzed C−H functionalization and photoredox nickel dual catalysis have emerged as innovative and powerful avenues for the synthesis of C‐branched glycosides. These two concepts have been recently established and provide efficient and mild methods for accessing a series of valuable complex C‐branched glycosides of great interest. Herein, recent developments in the synthesis of C‐branched aryl/alkenyl/alkyl glycosides through these two approaches are highlighted. Abstract : Transition‐metal‐catalyzed C−H functionalization and photoredox nickel dual catalysis have emerged as innovative and powerful avenues for the synthesis of C‐branched glycosides. This review highlights major developments in these processes as two powerful approaches for the synthesis of C‐branched glycosides.